Dual-column reinforced steel modular cabins in electrical infrastructure: component property and structural seismic performance - Liu, Zhixiang; Jin, Xingfu; Mu, Hong; Yang, Bo (Archives of Civil Engineering, 2026)
This study proposes a compact seismic reinforcement strategy for stacked steel modular cabins used in energy infrastructure construction. Modular construction offers significant benefits, including increased construction efficiency, reduced environmental impact, and improved safety. However, the seismic performance of modular structures presents unique challenges, particularly in earthquake-prone regions. To address these challenges, the paper presents a reinforcement method that incorporates corrugated steel plate walls at key structural locations, particularly at the lower corners of the ground floor. This approach is designed to improve lateral stiffness and energy dissipation without compromising construction simplicity or cost effectiveness. Finite Element Analysis (FEA) was used to evaluate the effectiveness of this method and demonstrated significant improvements in seismic performance. The results indicate that the proposed reinforcement reduces stress concentrations and mitigates interstory drift, thereby improving the overall structural resilience of the modular assemblies under seismic loading. The results provide a promising solution for balancing structural performance, ease of construction, and economic considerations in the context of seismic reinforcement for modular infrastructure.